Minimally invasive surgery for concomitant pericardial and diaphragmatic rupture after blunt trauma: a case report - Ranti Kenny Maila; Kenny Nyiko Mongwe; Mirza Mohamod Zahir Uddin Bhuiyan (Journal of Trauma and Injury)
Pericardial rupture with cardiac herniation is a rare injury that occurs following blunt trauma. It is even more unusual to find a pericardial tear associated with diaphragmatic injury after such trauma. Diagnosing this condition through radiologic imaging is challenging. A 51-year-old man was admitted to the emergency department after a wall collapsed on him. He reported overall body discomfort, breathlessness, chest pain, and abdominal discomfort. A plain x-ray revealed haziness in the left thoracic cavity and elevation of the left hemidiaphragm with collapse of the left lung. Additionally, a gastric shadow was seen within the left hemithorax, accompanied by a mediastinal shift to the right. An x-ray of the pelvis displayed fractures at the right sacroiliac joint, left superior pubic ramus, left inferior pubic ramus, and left anterior acetabular with displacement. A computed tomography scan indicated herniation of the stomach, splenic flexure, and spleen, but there was no clear evidence of pericardial laceration. The patient underwent emergency exploratory laparoscopy and thoracoscopy. During the laparoscopy, a significant defect was found in the left hemidiaphragm, along with a pericardial rupture that had led to cardiac herniation and visceral herniation of the stomach, splenic flexure, and spleen through the diaphragmatic tear. The abdominal visceral organs were repositioned into the abdomen, and the diaphragm was repaired. The heart was repositioned, and the pericardial defect was closed using thoracoscopic techniques. Pericardial rupture can be effectively managed using minimally invasive surgery.